The stock market reaction to the public announcement of a supranational list of too-big-to-fail banks during the financial crisis - Abreu, J. F.; Gulamhussen, M. A. (Journal of International Financial Markets, Institutions & Money, 2013)
In the aftermath of the global financial meltdown, regulators initiated a process to strengthen the regulation of too-big-to-fail (TBTF) banks with two goals: first, to increase the ability of these banks to absorb future financial shocks and second, to weaken the market expectation of public support for these banks in the event of a future financial crisis, thereby reducing the moral hazard problem associated with TBTF banks. We use an event study approach to analyze the market reaction to the official designation of a list of banks as TBTF by the Financial Stability Board (FSB) (on November 4, 2011). We do not find abnormal returns surrounding the FSB public announcement, which indicates that identifying the TBTF banks did not reduce the moral hazard problem.